Utilization of Technology as Learning Apercaption in Increasing Early Chilhood Learning Motivation at RA Masyithoh Wareng Butuh Purworejo - Mala, Lilik Sofwatul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2024)
The process of early childhood learning should be delivered pleasantly in order to get optimal results. In modern times, there are many advanced technologies that can help optimize the learning process. But in reality, the use of media has not been fully carried out by educators so that students' learning motivation decreases, especially during apercaptionactivities. This study aims to find out how the use of technology as a learning apercaptionactivity can increase early childhood learning motivation. This study used descriptive qualitative research method. The research setting was in RA Masyithoh Wareng, Butuh, Purworejo. Data sources were obtained from interviews with RA teachers, observations and documentation during research activities. The results of the study stated that all teachers have also used technology in the learning process, especially during apercaptionactivities, although with varying frequencies depending on needs. The biggest obstacle faced by teachers in utilizing technology is the limited number of equipment and some equipment conditions are not normal. Other obstacles are unstable internet connections and schools do not have backup power plants which result in very high dependence on electricity from PLN. The obstacles in terms of human resources are some teachers whose ability to use technology is still low. Utilization of technology in the apercaptionof RA MasyithohWarenglearningproven to be able to increase student learning motivation compared to the apercaptionof learning without using technologicalmedia